(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
Leadership effectiveness has traditionally relied on interpersonal skills, empathy, and emotional awareness. However, the rise of digital transformation introduces the integration of Artificial Intelligence (AI) with Emotional Intelligence (EI), reshaping leadership paradigms. This paper investigates how AI technologies—such as emotion recognition, natural language processing, and behavioral analytics—can simulate and enhance emotional intelligence in leadership contexts. The study reviews contemporary AI tools and real-world applications that support AI-powered EI in improving leadership functions like decision-making, team cohesion, conflict resolution, and employee engagement. AI-augmented EI demonstrates significant potential to enhance leadership effectiveness by providing deeper emotional insights and supporting adaptive behaviors. Challenges related to authenticity, ethical considerations, and the role of human intuition are also identified. The research proposes a future-ready leadership model that integrates human empathy with AI capabilities, fostering more inclusive, adaptive, and emotionally intelligent organizations.